Søren Kierkegaard et la littérature française - Billeskov Jansen, F. J. (KIERKEGAARDIANA, 1968)
Søren Kierkegaard et la littérature française. Søren Kierkegaard and French Literature, Eight Comparative Studies by Ronald Grimsley. Cardiff. University of Wales Press. 1966. 171 p.